Comment représenter la transgression de genre - L’Hermaphrodite dans l’oeuvre de J. K. Huysmans - - Stănică, Mihaela Gabriela (Nordlit, 2012)
By the end of the 19th century one may observe the birth of a particular form of knowledge which would further be known as scientia sexualis as well as the rationalization of the hermaphroditic body. Ernest Martin’s attempt to realize a taxonomy of the different forms of monstrosity (Histoire des monstres depuis l’Antiquité jusqu’à nos jours -1880) from a juridical and clinical perspective is representative for what Jean-Jacques Courtine will call “le désenchantement de l’étrange”. Since the physicians from that period refuse to acknowledge the existence of real hermaphrodites among humans, the pseudo-hermaphrodite will lose his ontological independence and will turn into a simple pathological deviation which will be placed among the other pathological figures which constitute the inventory of degenerations haunting the imaginary of the fin de siècle. Since the hermaphroditic body, this gender trouble that threatens the dual taxonomy of the society, is denied the ontological independence, this body enters the sphere of invisibility. Given that the transgressive body becomes a simple deviation, the hermaphrodite can only be a secondary representation. How are these mechanisms of the secondary representation applied to the literary productions of that period? The answer to this question could be found in Huysmans’ texts where the ambiguity of the hermaphroditic figure is captured into somatic and psychical representations that seem to confirm the epistemic paradigms of that fin de siècle.